Soymilk yield and quality as affected by soybean varieties and processing techniques - Ogundipe, H.; Dashiell, Kenton E.; Osho, S. (1989)
Grains of nine soybean varieties were processed into soybean milk, and their milk yield and protein (%) were determined, followed by sensory evaluations. In another experiment, grains of five soybean varieties were made into soybean milk, using five different processing techniques. In the first experiment, there was a significant difference among the varieties for milk yield and the sensory evaluation characters, but no significant difference for protein (%). In the second experiment, processing techniques. Variety and the processing technique x variety interaction all had a significant effect on milk yield.